2022
DOI: 10.1142/s0192415x23500064
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rd Inhibited Ferroptosis to Alleviate CCl4-Induced Acute Liver Injury in Mice via cGAS/STING Pathway

Abstract: Carbon tetrachloride (CCl4)-induced lipid peroxidation associated with hepatic oxidative stress and cell death is an important mechanism of acute liver injury (ALI). Ginsenoside Rd is considered an active ingredient of ginseng. Evidence suggests that ginsenoside Rd may improve ischaemic stroke, nerve damage, cancer and other diseases involving apoptosis, inflammation, oxidative stress, mitochondrial injury and autophagy. However, the effects of ginsenoside Rd on CCl4-induced ALI and its underlying mechanisms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…12 In cases of In addition to its established role in facilitating the innate immune response, alternative functions of STING signaling, including its involvement in apoptosis, ferroptosis, and autophagy, have been reported. [6][7][8] Prolonged activation of STING triggers mitochondriadependent apoptosis in B cells. 52 A STING agonist, diABZI, induces the cleavage of caspase 3 and contributes to the development of acute respiratory distress syndrome (ARDS).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In cases of In addition to its established role in facilitating the innate immune response, alternative functions of STING signaling, including its involvement in apoptosis, ferroptosis, and autophagy, have been reported. [6][7][8] Prolonged activation of STING triggers mitochondriadependent apoptosis in B cells. 52 A STING agonist, diABZI, induces the cleavage of caspase 3 and contributes to the development of acute respiratory distress syndrome (ARDS).…”
Section: Discussionmentioning
confidence: 99%
“…5 Apart from inflammatory responses, emerging studies suggest that activation of the STING is involved in various forms of cellular death processes, such as autophagy, ferroptosis, apoptosis, pyroptosis, and necroptosis. [6][7][8] Activation of the STING signaling pathway has been implicated in pathological changes associated with autoimmune diseases, infections, and CNS diseases. [9][10][11][12] Alcohol (ethanol, EtOH) is one of the most commonly consumed addictive substances worldwide and alcohol use disorder (AUD) is increasingly emerging as a significant global issue of concern.…”
Section: Introductionmentioning
confidence: 99%
“… 57 The inhibition of ferroptosis ameliorated acute liver damage by inhibiting STING activation. 65 However, STING signalling plays a crucial role in numerous forms of cell death, including ferroptosis. 66 , 67 Moreover, co-immunoprecipitation studies demonstrated that STING could interact with the TAK1 protein, indicating an interaction between STING and TAK1.…”
Section: Discussionmentioning
confidence: 99%
“…During acute kidney injury, elevated phosphoglycerate mutase 5 can dephosphorylate Bax, thereby promoting mtDNA leakage to trigger cGAS‐STING activation, progress critical in kidney pathogenesis [133]. Ginsenoside Rd, an active ingredient of ginseng, attenuates ferroptosis via inhibiting cGAS‐STING signaling from ameliorating CCl 4 ‐induced acute liver injury [137]. These various studies collectively suggest a central role of cGAS‐STING signaling in acute organ injuries via its intricate interaction with distinct types of cell death.…”
Section: Coordination Of Cgas‐sting and Cell Death In Human Diseasesmentioning
confidence: 99%